Applicability of ultrasound-guided puncture and laparoscopic cystectomy for ovarian endometriosis cyst: a non-randomized trial - Gulijianati Maowulieti; Lei Sun; Jingyao Wang; Jing Cheng; Yajie Yue; Hua Yuan (European Journal of Medical Research)
Abstract Background Ovarian endometriosis cysts are common gynecological conditions and are mostly benign. While many cysts resolve spontaneously, symptomatic or persistent cysts often require interventions. Laparoscopic cystectomy and ultrasound-guided puncture are the two primary therapeutic approaches for endometriosis cysts. How to select the suitable modality remains debated, particularly for patients with benign cysts who prioritize fertility preservation or who are at high surgical risks. Current guidelines lack consensus on optimal patient stratification, and decisions are often guided by pain severity, cyst size, and tumor markers. Objectives Few trials have directly compared the long-term outcomes of surgery versus puncture, such as recurrence and pain relief, especially in subgroups. This study aims to address this gap by evaluating efficacy based on objective endpoints while controlling for confounding factors. Methods Patients diagnosed with unilateral or bilateral ovarian endometriomas at Wuxi Maternity and Child Health Care Hospital were included in this non-randomized trial. They were categorized into two groups: patients who underwent laparoscopic cystectomy and patients who underwent ultrasound-guided puncture (UGP) intervention, with visual analogue scores (VAS), size and number of cysts, and fertility needs considered. All patients were followed up for 6 months. Results A total of 56 patients were included in this trail, including 28 patients in each group. The number of cysts and the number of patients with bilateral cysts were significantly higher in the surgery group than in the UGP group, while the size of cysts between the two groups showed no significant difference. The surgery group exhibited higher cure rates, while the UGP group showed lower cure rates at 3 months. The surgery group showed lower concentrations of cancer antigen 125 (CA-125), while the UGP group showed increased levels of postoperative anti-Müllerian hormone (AMH) after 6 months. VAS scores significantly decreased after laparoscopic cystectomy. Conclusions Laparoscopic cystectomy achieved better therapeutic effects than UGP at the 3-month follow-up. Laparoscopic cystectomy outperformed UGP in reducing CA-125 concentration and VAS scores at the 6-month follow-up, while UGP showed less impact on reproductive function. Trial registration This study is registered on the Medical Research Registration Information system ( https://www.medicalresearch.org.cn/login ), and has no registration number.